Influence of the chain length of surfactant in the modification of zeolites and clays. Removal of atrazine from water solutions. Issue 20 (18th October 2018) - Toledo-Jaldin, Helen Paola; Blanco-Flores, Alien; Sánchez-Mendieta, Víctor; Martín-Hernández, Osnieski
ABSTRACT: Removal potentials of a surfactant modified zeolite (SMZ) and clay (SMC) for atrazine adsorption were evaluated. Materials were modified with hexadecyl trimethyl ammonium bromide (HDTMA-Br) and benzyl octadecyl dimethyl ammonium (BODA) chloride considering the critical micellar concentration (CMC) of each one (0.94 and 0.041 meq/L, respectively). The influence of the surfactant was analyzed in detail, particularly the formation of surfactant layers (complete or partial) connected with the length of the surfactant tail (16 and 18 methyl groups or number of carbons in the chain). Raw materials were characterized by XRD and Fourier transform infrared spectroscopy (FTIR), SMZ and SMC were analyzed by FTIR. Results obtained from kinetic adsorption experiments shown that equilibrium time is less for materials modified with HDTMA (8 h) than materials with BODA (10 and 12 h). Materials modified with the largest chain surfactant (BODA) showed more resistance to atrazine masse transference. The chemisorption was presented in the adsorption mechanisms of atrazine and adsorbent materials. Based on the results of adsorption isotherms Langmuir isotherms showed the better correlation coefficients value. The qmax is greater for materials modified with BODA (0.9232 and 4.2448 mg/g) than for materials modified with HDTMA (0.6731 and 3.9121 mg/g). Therefore, SMZ and SMC modified with the largest chain surfactant has more affinity for the pesticide. The removal process at high concentration of atrazine depends of the partition process but at lower concentration, it occurs not only by this process but also by absorption process.